Pengaruh Cendawan Mikoriza Arbuskula Untuk Pertumbuhan dan Hasil Kacang Hijau (Phaseolus radiatus) Pada Tanah Bekas Galian C - Ai Nurlaila; Nurdin . (Wanaraksa, 2014)
This research is to see the effect of the use of the ArbuscularMycorrhizalFungi (AMF) and phosphorus on growth and yield of mung bean ( Phaseolus radiatus L. ) were carried out on a laboratory scale . The study is expected to evolve and ultimately provide complete information aboutthe technology of cultivation and appropriate commodity to be applied in land - mined land so that the land can be put to good use . Thus not only the economic benefits that will be obtained , but also environmental quality can be improved such as water management and land fertility .This study used a randomized complete block design with three levels of two factors treatments . The first factor is the AMF with a dose of 0 g / polybag , 10 g / polybag , and 20 g / polybag . The second factor is fertilizer P with a dose of 0 g / polybag , 5 g / polybag , and 10 g / polybag . Every treatment factorswererepeatedthree times.The results showedthatthere is an interaction between AMF treatment and P fertilizer on growth and yield components of green beans . Treatments that provide the most excellent effect on growth and yield are treated M2 ( 10 g AMF / hole ) and F2 ( 5 g SP - 36 / hole ) . Obtained an increase in yield of about 60 % when compared to the control treatment (without giving AMF and fertilizer P) .Keywords : AMF , Phosphorus , mung beans ( Phaseolus radiatus L.), growth, yield